New spleen tyrosine kinase inhibitors: patent applications published during 2011–2013. (September 2014) - Thorarensen, Atli; Kaila, Neelu
Spleen tyrosine kinase (SYK) is one of the more advanced small-molecule targets with regard to clinical development for treatment of inflammatory diseases. In this review we continue our analysis of the patent literature covering the time period 2011–2013. The analysis relates to any organization that has filed applications that explicitly discloses SYK as the intended target. In the last 2 years there has been a surge of application with a few new entries in a crowded field with the structural theme of compounds in these applications being a traditional type I ATP competitive inhibitor [1 ]. This overview of the SYK patent literature and the learning's of the inhibitors substitution patterns would be an important reading for anyone working in the area of SYK inhibitors.